2021
DOI: 10.1016/j.ctro.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

High-dose rate brachytherapy in localized penile cancer: 5-Year clinical outcome analysis

Abstract: Highlights Penile cancer is a rare tumor. The organ preservation perspective makes the treatment challenging. For early stage, conservative brachytherapy achieved excellent oncological outcome. Conservative brachytherapy reported encouraging functional results. HDR brachytherapy represents an attractive therapeutic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…We evaluated patient-reported symptoms while grading toxicity and included data on patient-reported GU toxicity (AUA scores). We utilized the NCI sponsored CTCAE v5.0 to evaluate toxicity, which is a standardized scoring criteria that has been utilized in many prospective brachytherapy studies [28] , [29] , [30] , [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated patient-reported symptoms while grading toxicity and included data on patient-reported GU toxicity (AUA scores). We utilized the NCI sponsored CTCAE v5.0 to evaluate toxicity, which is a standardized scoring criteria that has been utilized in many prospective brachytherapy studies [28] , [29] , [30] , [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
“…They observed a five-year local-relapse-free survival rate (LRFS) of 66%, with a penis preservation rate of 67% [ 10 ]. Recently, in our study [ 11 ] on 29 patients treated with multicatheter interstitial high-dose-rate brachytherapy (MHB), we found that the five-year LRFS rate was 82%. In our series, 93% of patients had radiodermatitis (grade 2: 83%).…”
Section: Discussionmentioning
confidence: 99%
“…Overall 3283 abstracts were screened and 235 studies were retrieved for full-text screening. Eighty-eight studies including 9758 patients were eligible for assessment: 16 NRCSs (1911 patients) [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] and 72 CSs (7864 patients) [6] , [7] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , …”
Section: Evidence Synthesismentioning
confidence: 99%
“…case series 201 N+: 9.95% BT Either LDR BT or pulse-dose rate BT (60 Gy) 70.15% (160/201) NR results per disease stage NR NR NR NR Acute local toxicity (mucositis/urethritis): 100% (201/201) Late painful ulceration: 43% (87/201) Meatal stenosis: 25.9% (52/201) Stenosis more frequent in radiation doses >60 Gy (10.3% vs 37.2%, p = 0.037) Painful ulceration: higher risk when dose rate >0.43 Gy/h (6.5% vs 30.7%, p = 0.021) 85% (95% CI 79–91) 32 patients required surgery for relapse (11 pGx, 14 Gx, 7 total penectomy) High risk Makarewicz et al (2010) [38] Retrosp. case series 33 T1: 23/33 (69.7%) T2: 7/33 (21.2%) T3: 3/33 (9.1%) N0: 100% HDR BT mean dose 51 Gy (48–54 Gy) given twice daily using HDR remote or 60 Gy applied for 6 consecutive days using PDR 78.8% (26/33) NR results per disease stage NR NR Erectile function is not affected after treatment (descriptive) NR Acute reactions limited to implant site: 33/33 (100%) Sterile distal urethritis: 10/33 (30.3%) Telangiectasia: 5/33 (15.15%) 84.85% (28/33) High risk Martz et al (2021) [39] Retrosp. case series 28(29) Tx: 1/29 (3.45%) T1: 22/29 (75.9%) T2: 6/29 (20.7%) N0: 26/29 (89.7%) Multicatheter HDR BT 35 or 39 Gy 82.76% (24/29) NR results per disease stage NR NR 14/29 (54%) were sexually active before BT 14/14 reported no change after surgery 25/29 (86%) reported mild LUTS before therapy No change reported after therapy Acute local toxicity (mucositis/urethritis): 100% (29/29) Telangiectasia: 17% (5/29) Necrosis: 10.3% (3/29) Urethral meatus stenosis: 2/29 (6.7%) 28/29 (96.55%) High risk Gambachidze et al (2017) [40] Retrosp.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation